AB0071 Characterization of NNC141-0100, a therapeutic antibody targeting inhibitory CD94/NKG2A receptors expressed in inflamed joints of rheumatoid arthritis patients. (23rd January 2014) - Pascal, V.; Sundström, Y.; Fasth, A.; Malmström, V.; Berg, L.; Kvist, P.H.; Spee, P.; Galsgaard, E.D.
Abstract : Background: CD94/NKG2A + CD56 bright Natural Killer (NK) cells represent the majority of NK cells in synovial fluid (SF) of Rheumatoid Arthritis (RA) patients and were proposed to exert an immunoregulatory role [1]. Prophylactic treatment with anti-NKG2A antibody fragment F(ab)'2 in murine collagen-induced arthritis reduced disease development by activating NK cells through blockade of its inhibitory receptor CD94/NKG2A [2]. Novo Nordisk A/S has generated an antagonistic, humanized anti-human NKG2A monoclonal antibody NNC141-0100 that blocks interaction between CD94/NKG2A and its ligand HLA-E. Objectives: The aim of this study was to characterize the binding specificity of NNC141-0100 and the expression pattern of its target, the CD94/NKG2A receptors, in peripheral blood (PB), SF and/or synovial tissue from RA patients and healthy donors (HD). Methods: CD94/NKG2A and HLA-E expression was investigated using flow cytometry, immunohistochemistry, digital image analysis and double-immunofluorescence (DIF) staining. Results: In PB and SF from HD or RA patients, NNC141-0100 binding correlated with expression of CD94/NKG2A as detected by another anti-NKG2A mAb, and was restricted to subsets of NK and T cells. We observed a similar distribution of CD94/NKG2A on PB lymphocytes from HD and RA patients where ∼50% of NK cells expressed CD94/NKG2A. In contrast, the majority (>90%) of NK cells in RA SF were CD94/NKG2A +, confirming the previously reported disease-associated accumulation of CD94/NKG2A + NK cells in RA SF [1]. CD94/NKG2A + distribution on T cells was similar in PB from HD and RA patients and in RA SF (∼3%). In RA synovial tissue CD94/NKG2A was expressed by the majority of NK cells and a small subset of T cells. CD94/NKG2A + cells were predominantly localized in lymphoid aggregates, but also present throughout RA synovium, whereas CD94/NKG2A + cells were absent in synovium from HD. The CD94/NKG2A + ligand, HLA-E, was detected on all infiltrating leukocytes in RA SF and synovium, at levels at least comparable to PB leucocytes from HD. Moreover, HLA-E was expressed by resident cells such as synoviocytes and endothelial cells in RA synovium. Conclusions: These data demonstrate that CD94/NKG2A and its ligand HLA-E are expressed at sites of inflammation in RA. NNC141-0100 specifically binds to CD94/NKG2A + NK cells accumulating in inflamed joints of RA patients, thus treatment with NNC141-0100 may promote the elimination of activated pro-inflammatory cells and suppress inflammation in RA patients. NNC141-0100 is currently being developed for the treatment of RA. References: Teixeira de Matos C et al. Activating and inhibitory receptors on synovial fluid natural killer cells of arthritis patients: role of CD94/NKG2A in control of cytokine secretion. Immunology 2007; 122 (2):291-301 Leavenworth JW et al. Mobilization of natural killer cells inhibits development of collagen-induced arthritis. Proc Natl Acad Sci USA 2011; 108 (35):14584-14589 Disclosure of Interest: V. Pascal Shareholder of: Novo Nordisk A/S, Employee of: Novo Nordisk A/S, Y. Sundström Grant/Research support from: Novo Nordisk A/S, A. Fasth Grant/Research support from: Novo Nordisk A/S, V. Malmström Grant/Research support from: Novo Nordisk A/S, L. Berg Grant/Research support from: Novo Nordisk A/S, P. Kvist Shareholder of: Novo Nordisk A/S, Employee of: Novo Nordisk A/S, P. Spee Shareholder of: Novo Nordisk A/S, Employee of: Novo Nordisk A/S, E. Galsgaard Shareholder of: Novo Nordisk A/S, Employee of: Novo Nordisk A/S